2010
DOI: 10.1002/chem.201000534
|View full text |Cite
|
Sign up to set email alerts
|

Enantiomer Resolution of Intrinsically Chiral C21‐Alkylated N‐Confused Porphyrin Complexes

Abstract: The resolution of stereoisomers of C21-alkylated nickel(II) complexes of N-confused porphyrin (NCP) was performed by means of chiral-phase HPLC with an effectiveness of above 90 % molar ratio for each isomer. The reverse signs of the Cotton effects in the circular dichroism (CD) spectra of the separated fractions are indicative of the pair of enantiomers. The application of low-temperature 2D NMR methods to the separated diastereomers of the system comprising a chiral 2-(S)-methylbutyl substituent, in connecti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
28
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 28 publications
(30 citation statements)
references
References 105 publications
2
28
0
Order By: Relevance
“…This ability utilizes a new principle of enantioselectivity, which is based upon only a two-point host-guest interaction mode in combination with the coupling electronic transitions of the chromophoric host, the relative orientation of which is totally controlled by the guest stereochemistry. Bis-porphyrinoids on the basis of C21-alkylated N-confused porphyrin served as other examples in this category [52]. Hence, the methylene-and o-xylene-linked bis-porphyrinoids, 56-58 (Figure 17), the binding modes of which involved one or two C21 atoms, were obtained and optically resolved.…”
Section: Chiral Porphyrinoids With Achiral Linkagementioning
confidence: 98%
“…This ability utilizes a new principle of enantioselectivity, which is based upon only a two-point host-guest interaction mode in combination with the coupling electronic transitions of the chromophoric host, the relative orientation of which is totally controlled by the guest stereochemistry. Bis-porphyrinoids on the basis of C21-alkylated N-confused porphyrin served as other examples in this category [52]. Hence, the methylene-and o-xylene-linked bis-porphyrinoids, 56-58 (Figure 17), the binding modes of which involved one or two C21 atoms, were obtained and optically resolved.…”
Section: Chiral Porphyrinoids With Achiral Linkagementioning
confidence: 98%
“…540 nm). The ortho-xylene linked system 62 consists of a C21-alkylated Ni(II) ion and an N2-alkylated metal-free NCP ligand (Figure 98), 121 the most pronounced CD band does not lie near the Soret-type band of the absorption spectrum at approximately 430 nm; therefore, the CD spectrum did not indicate excitonic coupling between the chromophores but rather exhibited a band morphology similar to that observed in the spectrum of the monomer. This result indicated that the NCP chromophores were relatively far from each other, which was confirmed by analysis of the solid-state structure, which revealed that the mean planes of the NCP were nearly perpendicular (Figure 99).…”
Section: Chemical Reviewsmentioning
confidence: 99%
“…121 For example, it has been demonstrated that the dimeric systems of 66a−66b, which are comprised of coordinating linkages between the optically active moieties via the Pt(II) ion, are diastereoselective (Figure 104). 121,225 The system remains chiral due to differing coordination modes for the subunits and the rigid helical structure. The enantiomers have CD spectra that are near perfect mirror images (Figure 105).…”
Section: Chemical Reviewsmentioning
confidence: 99%
“…15d), 90,91 and so on. [92][93][94][95][96][97][98][99] Additionally, oxidation of Ni II (NCTTP 2À ) in pyridine gives Ni III (21-oxo-NCTTP 3À )(py) (Fig. 15b).…”
Section: Ni Pd and Pt Complexes (Group 10)mentioning
confidence: 99%